Использование образовательных Интернет – ресурсов для подготовки к сдаче международного тестирования IELTS - Амирова, Е.Л. (My University, 2016)
The article presents the analysis of Internet resources, which can be used for preparation for IELTS examination. The definitions of notions “Internet resource” is given, the structure of test, criteria of speaking and writingevaluation are observed, suitable Internet resources for development skills of listening, reading, speaking and writing in English are explored.
Keywords: Internet resource; intercultural examination IELTS; criteria of IELTS evaluation; Internet resources for preparation for IELTS